Pengaruh Ukuran Perusahaan, Konsentrasi Kepemilikan, Leverage, Profitabilitas Dan Price To Book Value Terhadap Tingkat Pengungkapan Sukarela Asset Tidak Berwujud - Jasmadeti, Jasmadeti; Wahyuni, Wulan (Jurnal Ilmiah Manajemen Kesatuan, 2019)
This study aims to identify the influence of firm size, ownership concentration, leverage, profitability and price to book value on voluntary disclosure of intangible assets of the listed manufacturing in Indonesia Stocks. The samples of this research consist of 10 manufacturing companies at Indonesia Stock Exchange during 2011-2015 periods and selected by purposive sampling. The data used are secondary ones, which are annual financial statements of the 10 manufacturing companies’ samples. The method of data analysis used in this study to prove the hypothesis are descriptive statistics, classic assumptions test, multiple regression models and the determinant coefficient. The Findings of this study, shows that four out of five independent variables had no significant effect to the level of intangible assets voluntary disclosure, they are firm size, ownership concentration, leverage, profitability. Only price to book value influences to the level of intangible assets voluntary disclosure significantly.